2017
DOI: 10.1155/2017/5437139
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by Polymyxin E Is Involved in Rapid Killing ofPaenibacillus polymyxa

Abstract: Historically, the colistin has been thought to kill bacteria through membrane lysis. Here, we present an alternative mechanism that colistin induces rapid Paenibacillus polymyxa death through reactive oxygen species production. This significantly augments our understanding of the mechanism of colistin action, which is critical knowledge toward the yield development of colistin in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Accumulating evidence suggests that the hydroxyl radical death pathway could be activated as a downstream event of colistin exposure [ 88 , 89 ]. The fact that MCR-3 can modify lipid A moieties of LPS on bacterial membrane, an initial target of colistin, allowed us to hypothesize that expression of MCR-3 might physiologically prevent colistin-induced ROS production.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that the hydroxyl radical death pathway could be activated as a downstream event of colistin exposure [ 88 , 89 ]. The fact that MCR-3 can modify lipid A moieties of LPS on bacterial membrane, an initial target of colistin, allowed us to hypothesize that expression of MCR-3 might physiologically prevent colistin-induced ROS production.…”
Section: Methodsmentioning
confidence: 99%
“…Paenibacillus polymyxa is a multifunctional Gram-positive (G + ) bacterium that has been reported to have applications in agriculture ( Hao and Chen, 2017 ), medicine ( Galea et al, 2017 ; Yu et al, 2017 ), and industry ( Lal and Tabacchioni, 2009 ). P. polymyxa has been in the list of substances reported under the Toxic Substance Control Act (TSCA) by the United States Environmental Protection Agency (EPA) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymyxins contain six cationic inner membrane (5)(6)(7). Although LPS is absent in Gram-positive bacteria, recent studies showed that polymyxins can also kill their producer, P. polymyxa, in a manner mediated by both cell membrane damage and oxidative stress (8)(9)(10).…”
mentioning
confidence: 99%